Determinants of Insulin Resistance Beyond Adiposity: A Multivariable Analysis in Normal-Weight Adults - Aycan Acet; Türkan Paşalı Kilit; Sertaş Erarslan; Cumali Yalçın; Can Özlü; Çağla Özdemir (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Insulin resistance (IR) is a key pathogenic mechanism in Type 2 Diabetes Mellitus, often linked to obesity-related inflammation. However, IR can also occur in individuals with normal weight, a condition known as the metabolically obese normal-weight phenotype. This study assesses the predictive value of routine hematological parameters compared to combined inflammation indices for detecting IR in non-obese populations. This retrospective cross-sectional study included 305 normal-weight adults (body mass index < 25 kg/m²). IR was defined by a Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) threshold of 2.5. Parameters were analyzed using univariate and hierarchical multivariable logistic regression. Parallel models, adjusted for age, sex, and body mass index (BMI), were used to assess individual leukocyte subtypes. Discriminatory performance was evaluated through Receiver Operating Characteristic (ROC) curve analysis. IR was found in 93 (30.5%) participants. The IR+ group exhibited significantly higher BMI, glucose, triglycerides, HbA1c, and white blood cell (WBC) counts (p < 0.05). Multivariable analysis identified WBC count as the only independent predictor of inflammation (OR = 1.946, p < 0.001). WBC count showed better explanatory power (Nagelkerke R2 = 0.196) and discriminatory ability (AUC = 0.725) compared to individual subtypes and composite indices, like the panimmune inflammation value (AUC = 0.510). The final multivariable model achieved an AUC of 0.736. In normal-weight adults, IR appears to exhibit a more pronounced association with generalized systemic inflammation reflected by absolute WBC counts rather than ratio-based indices. WBC count serves as a practical marker for early metabolic risk identification in non-obese individuals.